Risk Factors Associated with Hypertensive Patients at Baquba Teaching Hospital - Hussein, Mohammed Ali; Noaman, Aqeel Abbas; Aboud, Ali Abass (Diyala Journal of Medicine, 2019)
Background:Hypertension is one of the most common disorders affecting on the heart,blood vessels , brain and kidney and it is considered is a very common disease and frequent with diabetes , Conversely, it is responsible for one of four premature deaths in developed countries. Objective: To evaluate the most important factors that cause hypertensive and to study their effects on patients . Patients and Methods: This study was conducted at Baquba Teaching Hospital in the recovery unit for the period from 1/10/2017 until 1/3/2018 The study included 100 patients with hypertensive (44 male , 56 female) to compare them with 25 healthy persons (11 male , 14female) , was measuring blood pressure and has been done a questionnaire for each patient included (Age, BMI , Smoking , Number of hours sleep , Drinking beverages , Chronic diseases) and then by revulsion (2 cc) of blood to measured fasting blood glucose . Results: The results of the study indicates that there is a significant differences at p<0.05 levels of systolic blood pressure , fasting blood glucose , hours of sleep , soft drinks , chronic diseases , smoking . Conclusion: The increase in smoking , soft drinks affects on the level of blood pressure directly, and the decrease of sleep associated with high blood pressure , and most diabetics patients are more prone to hypertension.